MicroRNA-223-3p downregulates the inflammatory response in preeclampsia placenta via targeting NLRP3 - Xueqiong Liu; Zhiyue Li; Dan Lu (BMC, 2024)
Abstract Objective To investigate the regulatory role of miR-223-3p in the inflammatory response of PE placenta. Methods PE and normal placental tissues were collected to measure the expression of NLRP3 and miR-223-3p. The targeting relationship between NLRP3 and miR-223-3P was verified by bioinformatics analysis and classical double-luciferase reporter gene assay. Lipopolysaccharide (LPS) was used to induce HTR8/SVneo cells as PE placental cell inflammation model. Then we transfected miR-223-3p overexpression/miR-223-3p negative control plasmid into the LPS-induced HTR8/SVneo cells. Next, the expressions of NLRP3, Caspase-1, GSDMD, IL-1β and IL-18 were evaluated to elucidate the regulatory effect of miR-223-3p on the inflammatory response mediated by NLRP3 in PE placenta. Results Compared with normal controls, NLRP3 was significantly up-regulated in PE placenta, while miR-223-3p was down-regulated. In addition, NLRP3 was a direct target of miR-223-3p. Further research revealed that the expression of NLRP3, Caspase-1, GSDMD, IL-1β and IL-18 could be obviously promoted in HTR8/SVneo cells treated with LPS (500 ng/ml) for 24 h, nevertheless it could be significantly suppressesed under the overexpression of miR-223-3p. Conclusion MiR-223-3p suppressed NLRP3 inflamariomes activation, downstream inflammatory factors secretion and pyroptosis in LPS-induced HTR8/SVneo cells indicating that miR-223-3p could serve as an anti-inflammatory factor in preeclampsia.